Simultaneous detection of G6PD mutations using SNPscan in a multiethnic minority area of Southwestern China - Wei, Huagui; Wang, Chunfang; Huang, Weiyi; He, Liqiao; Liu, Yaqun; Huang, Huiying; Chen, Wencheng; Zheng, Yuzhong; Xu, Guidan; Lin, Liyun; Wei, Wujun; Chen, Weizhong; et al. (Frontiers in Genetics, 2023)
Objectives: Baise, a multiethnic inhabited area of southwestern China, is a historical malaria-endemic area with a high prevalence of G6PD deficiency. However, few studies of G6PD deficiency have been conducted in this region. Therefore, we performed a genetic analysis of G6PD deficiency in the Baise population from January 2020 to June 2021. Methods: A SNPscan assay was developed to simultaneously detect 33 common Chinese G6PD mutations. Validation of the method was performed using 30 G6PD-deficient samples. Then, a total of 709 suspected G6PD-deficient samples collated from the Baise population were evaluated for G6PD status, type of mutation and effect of mutations. Results: The sensitivity of the SNPscan assay for detecting G6PD mutations was 100% [95% confidence interval (CI): 94.87-100%] with a specificity of 100% (95% CI: 87.66-100%). A total of fifteen mutations were identified from 76.72% (544/709) of the samples. G6PD Kaiping (24.12%) was found to be the most predominant mutation, followed by G6PD Canton (17.91%) and G6PD Gaohe (11.28%). In the homozygous or hemizygous status, the enzyme activity of Class III G6PD mutations (1.0-1.0 KU/L) was significantly higher than that of Class II G6PD mutations (1.0-1.0 We compared the G6PD mutation spectrum among Zhuang, Han and other Southeast Asian populations, and the Zhuang population's mutation distribution was quite similar to that in the Han population. Conclusions: This study provided a detailed G6PD mutation spectrum in Baise of southwestern China and will be valuable for the diagnosis and research of G6PD deficiency in this area. Furthermore, the SNPscan assay could be used to quickly diagnose these G6PD mutations accurately.